Case Report: Zellweger Syndrome and Humoral Immunodeficiency: The Relevance of Newborn Screening for Primary Immunodeficiency - Fazi, C.; Lodi, L.; Magi, L.; Canessa, C.; Giovannini, M.; Pelosi, C.; Pochiero, F.; Procopio, E.; Donati, M. A.; Azzari, C.; Ricci, S. (Frontiers in Pediatrics, 2022)
Background Zellweger syndrome (ZS) is a congenital autosomal recessive disease within the spectrum of peroxisome biogenesis disorders, characterized by the impairment of peroxisome assembly. The presence of peroxisome enzyme deficiencies leads to complex developmental sequelae, progressive disabilities, and multiorgan damage, due to intracellular accumulation of very-long-chain fatty acids (VLCFAs). Case Presentation We report the case of an infant affected by ZS in which agammaglobulinemia, detected through neonatal screening of congenital immunodeficiencies, appeared as a peculiar trait standing out among all the other classical characteristics of the syndrome. The exome analysis through next-generation sequencing (NGS), which had previously confirmed the diagnostic suspicion of ZS, was repeated, but no mutations causative of inborn error of immunity (humoral defect) were detected. Conclusion In this case, no genetic variants accountable for the abovementioned agammaglobulinemia were detected. Given that the scientific literature reports the involvement of peroxisomes in the activation of Nuclear Factor κ-light-chain-enhancer of activated B cells (NF-κB) pathway, which is crucial for B-cell survival, with this work, we hypothesize the existence of a link between ZS and humoral immunodeficiencies. Further studies are required to confirm this hypothesis.